Mengembangkan Potensi Energi Terbarukan Di Jaringan Irigasi Dengan Pembangkit Listrik Tenaga Mikro Hidro (Pltmh) - Suwignyo . (Department of Civil Engineering, Faculty of Engineering, University of Muhammadiyah Malang, 2011)
Power Generation Potential Micro Hydro Mini & Micto Hydro (PLTM & PLTMH) in Indonesia reached 0.45 GWatt, has been developed for 0084 GWatt (18%). One potential PLTM & PLTMH is irrigation networks, both new irrigation networks and existing irrigation networks. Wide of †rice fields in Indonesia are 6134 million ha, consisting of 19,344 technical irrigation network mainly scattered in the island of Java, Sumatra, Sulawesi, Bali and West Nusa Tenggara Province. Year 2005 has been successfully built the capacity of 100 kW PLTMH Melong exploit irrigation networks were involved networks fall building in Curug Agung in Subang district. PLTMH produced 700,800 KWh of energy per year, medium voltage network interconnected with PLN. In April 2008 this power of Micro Hydro Power (PLTMH) with a capacity of 100 kW operating in Campus University Muhammadiyah of Malang (UMM) and this is collaboration result of UMM with the National Research and Development ( Balitbang) Ministry of Energy and Mineral Resources of Indonesia. UMM PLTMH Development is to promote the use of renewable energy sources as part of efforts to overcome the energy crisis as well as efforts to decrease greenhouse gas emissions that cause global warming. One type of renewable energy sources are small -scale water or micro- hydro. Development of PLTM & PLTMH in irrigation networks can be done in the main building, building falls, and buildings structures to complement that have a high hydraulic fall. The study on an irrigation network D.I. in Kedungkandang Malang shows that the potential power in buildings comes up in irrigation on the main channel reaches about 1 MWatt.Key words: power, micro hydro, irrigation channels